Pd/ZnO Nanoparticles Based Schottky Ultraviolet Photodiodes Grown on Sn-Coated n-Si Substrates by Thermal Evaporation Method - Somvanshi D.; Jit S. (My University, 2025)
This paper reports the ultraviolet (UV) detection characteristics of Pd/ZnO nanoparticles (NPs) based Schottky diodes grown on Sn coated n-Si substrates by thermal evaporation method. The measured current-voltage characteristics of the Pd/ZnO NPs/Sn/n-Si diodes under both the dark and UV illumination at wavelength of 365 nm have been presented for the applied bias voltage varying from -3 to 3 V. The as-fabricated photodiodes show a high-contrast ratio (i.e., the photocurrent to dark current ratio) of ∼541.34, an excellent quantum efficiency of ∼68%, a reasonably good responsivity of ∼0.20 A/W at 365 nm, and -3 V reverse bias voltage at room temperature. © 1995-2012 IEEE.